A Primer on Asian Americans and Asian American Studies for Public Administration. (22nd November 2022) - Lee, C. Aujean; Forney, Aarika
Abstract: This article serves as an introduction for public administration and public institutions about Asian Americans. The experiences of Asian Americans and the field of Asian American Studies can inform a more nuanced understanding of how racial categories are constructed and community-led efforts that lead to institutional change. Asian Americans offer important insights for public administration, including how to contend with intra- and intergroup differences, how racialization upholds white supremacy, and how to document community-based histories of activism and engagement with public institutions. We end with recommendations to rethink diversity and racial climate in the field. Through a more in-depth understanding of racial categories, public institutions can improve resource distribution and decision-making.